Experimental determination of the extent of Fe(III) reduction and Fe isotope fractionation during microbial reduction of ferrihydrite in freshwater systems by sulfate-reducing bacteria - Zhang, Yan (University of Waterloo, 2017)
Traditionally, sulfur was thought to have little influence on Fe cycling in freshwater systems because of the low sulfate concentrations (average ~ 0.2 mM) in such waters. However, a recent study suggested that a cryptic sulfur cycle exists for freshwater systems, as it does in more sulfate-rich marine environments. Therefore, sulfur cycling could be a driving factor of Fe redox cycling even in low-sulfate conditions. To test the hypothesis that cryptic sulfur cycling significantly influences Fe cycling in sulfate-poor freshwater environments, this study reports Fe concentration and isotope data during sulfide-induced Fe reduction and direct enzymatic Fe reduction by two sulfate-reducing bacteria (SRB): Desulfovibrio vulgaris (D. vulgaris), which is capable of reducing chelated Fe(III) as well as insoluble Fe(III) oxides enzymatically, and Desulfobacter curvatus (D. curvatus), which cannot enzymatically reduce Fe(III). Four experimental sets were performed to infer the main controls on the extent of Fe(III) reduction: (i) 0.2 mM abiotic sulfide and Si and ferrihydrite co-precipitates (Si-HFO) (ii) SRB (D. vulgaris) and Si-HFO, (iii) 0.2 mM enzymatically produced sulfide (from D. vulgaris or D. curvatus) and Si-HFO with the absence of D. vulgaris, and (iv) 0.2 mM sulfate, SRB (D. vulgaris or D. curvatus), and Si-HFO. The abiotic and enzymatically produced sulfide experiments yielded similar extents of Fe(III) reduction. By contrast, direct enzymatic Fe(III) reduction by SRB (D. vulgaris) was less efficient. The experiment with SRB and Si-HFO in the presence of sulfate had the highest extent of Fe(III) reduction. This extent is higher than the total of simply (ii) plus (iii), thus confirming the presence of a cryptic S cycle at low-sulfate conditions. To investigate how SRB influences Fe isotope fractionation during Fe(III) reduction, two experiment sets were performed: (i) SRB (D. vulgaris) and 0.7 mM Si-HFO, and (ii) 0.2 mM enzymatically produced sulfide (from D. vulgaris) and 0.7 mM Si-HFO. With increased extent of Fe(III) reduction, δ56Feaq significantly increased, δ56Fesolid slightly increased, and δ56Fesorb slightly decreased. The most positive and negative δ56Fe values were 0.48 ± 0.48‰ (2σ; n = 6) and -1.39 ± 1.30‰ (2σ; n = 6) in the solid phase and aqueous phase, respectively, from the experiment with enzymatically produced sulfide. The Fe isotope fractionation between Fe(II)aq and Fe(III)solid (Δ56FeFe(II)aq –Fe(III)solid) in both experiments was inversely correlated with the extent of Fe(III) reduction during the duration of the experiments (20 days). However, based on previous studies, iii equilibrium Fe isotope fractionation was expected for redox changes. Thus, if a longer experiment had been performed, the Fe isotopes may have continued to exchange until the system reached equilibrium. The Δ56FeFe(II)aq –Fe(III)solid in the experiments with enzymatically produced sulfide and with SRB (D. vulgaris) ranged from -1.22‰ to -4.14‰ with an average of -2.92 ± 2.60‰ (2σ; n = 4), and from -0.04 to -0.86‰ with an average of -0.39 ± 0.68‰ (2σ; n = 4), respectively. From previous studies, Δ56FeFe(II)aq –Fe(III)solid was ~-3‰ with the presence of dissimilatory Fe reducing bacteria (DIRB) (such as Shewanella oneidensis and Geobacter sulfurreducens). Hence, Fe isotope fractionation by enzymatically produced sulfide is similar to that observed for DIRB or abiotic systems whereas Fe isotope fractionation by SRB is significantly smaller. This study confirms that the same mechanism of Fe isotope fractionation occurs during dissimilatory Fe reduction (DIR) regardless of Fe substrate, but a different mechanism of Fe isotope fractionation occurs during DIR caused by SRB compared to DIRB. This result further suggests that Fe isotopes have the potential to be applied as a tracer to evaluate different microbial pathways for Fe(III) reduction, specifically: 1) enzymatically by SRB versus enzymatically by DIRB; and 2) enzymatically by SRB versus non-enzymatically by sulfide.
Keywords: Fe isotope; Freshwater; sulfate-reducing bacteria